Incidence and mortality of proximal and distal colorectal cancer in Germany: trends in the era of screening colonoscopy - Cardoso, Rafael; Zhu, Anna; Guo, Feng; Heisser, Thomas; Hoffmeister, Michael; Brenner, Hermann (Deutsches Ärzteblatt, 2021)
Background: The use of colonoscopy has increased and colorectal cancer (CRC) incidence has decreased after the introduction of screening colonoscopy in Germany. However, it remains unknown to what extent progress has been achieved in the prevention of cancer in the proximal colon, distal colon, and rectum. - Methods: We analyzed trends in CRC incidence (2000-2016) and mortality (2000-2018) in Germany by sex, age, and tumor location. - Results: The age-standardized incidence of CRC declined by 22.4% (from 65.3 to 50.7 per 100 000) in men and by 25.5% (from 42.7 to 31.8 per 100 000) in women. CRC mortality declined by 35.8% (from 29.6 to 19.0 per 100 000) in men and by 40.5% (19.0 to 11.3 per 100 000) in women. Despite demographic changes, the annual numbers of CRC cases and deaths still decreased from about 60 400 to 58 300 and from around 28 700 to 24 200, respectively. The decline in incidence was greatest in groups aged ≥ 55 years. While the incidence of cancer in the distal colon and rectum decreased by 34.5% and 26.2%, respectively, in men and by 41.0% and 27.9% in women, the incidence of proximal colon cancer remained stable in men and decreased by only 7.0% in women. However, a major shift towards earlier stages was observed for the proximal cancers. - Conclusion: The results support the assumption that the increased use of colonoscopy has contributed to substantial reductions in the incidence of distal CRC incidence and the mortality from cancers in the entire colon and rectum.